Signaling Character in Electoral Competition - Kartik, Navin; McAfee, R. Preston (American Economic Review, 2007)
We study a one-dimensional Hotelling-Downs model of electoral competition with the following innovation: a fraction of candidates have “character” and are exogenously committed to a campaign platform; this is unobservable to voters. Character is desirable, and a voter's utility is a convex combination of standard policy preferences and her assessment of a candidate's character. This structure induces a signaling game between strategic candidates and voters, since a policy platform affects voters' utilities not only directly, but also indirectly through inferences about a candidate's character. The model generates a number of predictions, starting with a failure of the median voter theorem. (JEL D72, D82)